A clamped feedback based digital versatile optimal bidirectional battery charger for HEV/PHEV - Chitransh V.; Singh A.; Singh R.K. (My University, 2025)
Due to the increasing awareness and adoption of eco-friendly vehicle technologies, hybrid electric vehicle (HEV) and plug-in hybrid electric vehicle (PHEV) technologies have become one of the most interesting areas of research because of the reduced use of fuel and green house emission. Battery chargers are one of the most important parts in developing the HEV's and PHEV's. The various existing optimal battery charging techniques are constant current (CC)-constant voltage (CV) charging, pulse charging and reflex charging. The major problem with these conventional optimal battery charging techniques are that different circuits are needed for adopting different optimal charging techniques. This paper presents design and implementation of a field programmable gate array (FPGA) based versatile optimal bidirectional digital battery charger for HEV/PHEV. The proposed digital optimal charger is capable of adapting all the existing optimal battery charging techniques i.e., constant current-constant voltage (CC-CV) charging, Pulse charging and Reflex charging in a single circuit. The proposed system uses a bidirectional magnetically coupled inductor topology with a damping network. When the proposed system adapts CC-CV charging technique, it shows automatic and smooth transition from CC to CV mode without using any extra switching circuit and when the proposed system adapts pulse and reflex charging techniques it gives regulated charging and discharging currents. Modeling, analysis, and simulation have been carried out on a 250W prototype to validate the proposed algorithm. © 2015 IEEE.